2017
DOI: 10.12973/eurasia.2017.00707a
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Grade Study Validating the Evolutionary Pathway of Student Mental Models in Electric Circuits

Abstract: Cross-grade studies are valuable for the development of sequential curriculum. However such studies are time and resource intensive and fail to provide a clear representation to integrate different levels of representational complexity. Lin (Lin, 2006;Lin, Chiu, & Hsu, 2006) proposed a cladistics approach in conceptual evolution to construct a hypothetical Conceptual Evolution Tree (CET; also called Evolutionary Pathway of Student Mental Models) in electric circuits which overcome the limitations of earlier cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 23 publications
1
12
1
1
Order By: Relevance
“…The present research revealed that employing a mixed method generates different results from, previous researches (Lin, 2017). Research findings suggested that the PBL learning model improved the students' mental models of elasticity.…”
Section: Discussioncontrasting
confidence: 56%
“…The present research revealed that employing a mixed method generates different results from, previous researches (Lin, 2017). Research findings suggested that the PBL learning model improved the students' mental models of elasticity.…”
Section: Discussioncontrasting
confidence: 56%
“…CET provides a representation of the evolutionary pathways of students' mental models about a specific topic, and can be verified by cross-grade investigation or previous empirical studies. Several topics have been explored and validated by cross-grade investigation in our team, such as electric circuit (Lin, 2006(Lin, , 2017, phase transitions , shape of the earth (Wu & Lin, 2013), and ideal gas (Chiu, Wu, Chung, Li, & P., 2013).…”
Section: Methodological Perspectivementioning
confidence: 99%
“…E. F first set the education as an input to human capital (Denison, 1983;, and made a research to calculate "the return of educational capital" to measure "the contribution of education investment to the economy", and in China, many scholars have made great achievement in the quantitative measurement of the contribution rate of higher education investment to regional economic growth ( Hui Min Qian, 2013;Lin, 2017;Song et al, 2017).…”
Section: The Contribution Rate Of Educational Input To Industrial Ecomentioning
confidence: 99%
“…According to Sara's summary of residents' anxiety type about recycled water reuse, it can be seen that residents' concerns about recycled water reuse are mainly about not only the health risks that recycled water reuse may bring to themselves and their family members but also the impact on the local environment. Thus, this section focuses on investigating residents' risk perception for recycled water reuse from these two aspects (Ross, 2014;Lin, 2017). In order to simplify the calculation of the directness of each potential variable, the data x'= 8-x is adjusted after the risk-perception facet data of recycled water reuse is substituted into the forward data direction of the model, if the original data is x.…”
Section: Variables Definitionmentioning
confidence: 99%